CODE-SWITCHING IN ZHAFIRA AQYLA YOUTUBE VIDEO: A SOCIOLINGUISTIC STUDY - Parinduri, Afrahul Fadhillah; Chaterina Manalu, Lidya Arella; Lekson, Mutiara Alda; Alfia, Fila; Rangkuti, Rahmadsyah (SIGEH ELT : Journal of Literature and Linguistics, 2024)
This study investigates the phenomenon of code-switching in the YouTube video titled "Alasan Aku Milih S2 di Harvard Walau Tanpa Beasiswa" by Zhafira Aqyla, an Indonesian YouTuber and Harvard graduate. The research focuses on identifying the types and functions of code-switching in her video using a sociolinguistic framework. Poplack's typology of code-switching—comprising inter-sentential, intra-sentential, and tag-switching guides the analysis. The results show that intra-sentential switching is the dominant type, making up 89.48% of the occurrences. This frequent integration of Indonesian and English within sentences suggests the speaker's ease in navigating both languages to convey ideas more precisely and efficiently. The study also highlights the influence of Zhafira's international educational background and professional environment on her code-switching behaviour, emphasizing her bilingual identity. These findings contribute to the broader understanding of bilingualism in social media contexts, particularly among educated individuals in global settings.